Analysis of human papillomavirus type 16 E4, E5 and L2 gene variations among women with cervical infection in Xinjiang, China - Haozheng Cheng; Yangliu Dong; Le Wang; Xian Zhao; Xiangyi Zhe; Dongmei Li; Hongtao Li; Renfu Shao; Jing Tuo; Zemin Pan (BMC, 2024)
Abstract Background There is a high incidence of cervical cancer in Xinjiang. Genetic variation in human papillomavirus may increase its ability to invade, spread, and escape host immune response. Methods HPV16 genome was sequenced for 90 positive samples of HPV16 infection. Sequences of the E4, E5 and L2 genes were analysed to reveal sequence variation of HPV16 in Xinjiang and the distribution of variation among the positive samples of HPV16 infection. Results Eighty-one of the 90 samples of HPV16 infection showed variation in HPV16 E4 gene with 18 nucleotide variation sites, of which 8 sites were synonymous variations and 11 missense variations. 90 samples of HPV16 infection showed variation in HPV16 E5 and L2 genes with 16 nucleotide variation sites (6 synonymous, 11 missense variations) in the E5 gene and 100 nucleotide variation sites in L2 gene (37 synonymous, 67 missense variations). The frequency of HPV16 L2 gene missense variations G3377A, G3599A, G3703A, and G3757A was higher in the case groups than in the control groups. Conclusions Phylogenetic tree analysis showed that 87 samples were European strains, 3 cases were Asian strains, there were no other variations, and G4181A was related to Asian strains. HPV16 L2 gene missense variations G3377A, G3599A, G3703A, and G3757A were significantly more frequent in the case groups than in the control groups.